Increasing the Photochemical Performance of Dye-Sensitized Solar Cell: The Effect of Mixed Dye from Areca Catechu and Tectona Grandis Extract - Ahmad, Ali; Hasan, Abu; Bow, Yohandri (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Dye Sensitized-Solar Cells (DSSC) represent a solar cell technology belonging to the third generation, functioning on the principles of the photoelectrochemical concept. The utilization of teak leaves (Tectona Grandis) and areca nut (Areca Catechu) as an organic dye in DSSC is accountable for the absorption of solar radiation. The stimulation of electrons induced by light in photocatalysis is greatly impacted by the band gap's specific location. For a material to act efficiently as a photocatalyst, it must possess a conduction band exhibiting a notably high positive potential in comparison to the potential of electron acceptance. The mixed of dye from teak leaves and areca nut increasing the absorption of the sunlight, thereby enhancing light absorption. The current study details the Mixing of areca nut and teak leaves extract to enhance the photochemical performance of DSSC and subsequently examined via FTIR, and UV-Vis analyses. A thorough examination of samples from mixed dye significantly impacts the elemental composition, and optical characteristics of the substance. The outcomes revealed that mixed dye from areca nut and teak leaves exhibited the most notable enhancement in DSSC efficiency, followed by teak leaves dye, whereas the areca nut dye demonstrated least performance potential. These findings offer valuable insights towards optimizing dye to boost the efficiency of DSSC.